Impact of falling on social participation and social support trajectories in a middle-aged and elderly European sample. (December 2016) - Pin, Stéphanie; Spini, Dario
Abstract: Whereas falls are frequent and traumatic events for the elderly, their long-term consequences in terms of the social lives of older fallers are understudied. This study aimed to identify the impact of falling on the trajectories of social participation and social support of older people in Europe. Our sample consisted of 16, 583 people aged 50–95 years from 10 European countries who responded to the waves 1, 2 and 4 of the Survey of Health Ageing and Retirement in Europe. The impact of falling on the trajectories of social participation and social support was examined using generalised estimating equation (GEE) models. The effect of the interactions between falling and frailty and between falling and social support on social participation was assessed. Falls were negatively associated with social participation (OR=0.73, p <0.001) and positively associated with social support (OR=2.20, p <0.001). For social participation, this effect was moderated by frailty; the interaction term between frailty and fall highlighted the finding that frailty better explained the global trajectory of social participation compared with falling. Social support did not buffer the negative impact of falling on social participation. Falls can be considered stressful events that have implications beyond the health context. Frail people who have fallen should be targeted in prevention and rehabilitation programmes; specific attention should also be paid to the relatives of fallers, who appeared to be more intensively solicited after a fall. Highlights: Fall events were independent and direct predictors of increased social support. Falls indirectly decreased social participation. Frail people exhibited the lowest odds of social participation after a fall and should be targeted in fall prevention programmes. Specific attention should be paid to informal caregivers, who provided increasing support after a fall.